Current and Emerging Approaches for Hepatic Fibrosis Treatment - Jingguo Li; Biguang Tuo (Gastroenterology Research and Practice)
Liver fibrosis resulting from chronic liver injury is a key factor to develop liver cirrhosis and risk of hepatocellular carcinoma (HCC) which are major health burden worldwide. Therefore, it is necessary for antifibrotic therapies to prevent chronic liver disease progression and HCC development. There has been tremendous progress in understanding the mechanisms of liver fibrosis in the last decade, which has created new opportunities for the treatment of this condition. In this review, we aim to make an overview on information of different potential therapies (drug treatment, cell therapy, and liver transplantation) for the liver fibrosis and hope to provide the therapeutic options available for the treatment of liver fibrosis and discuss novel approaches.